2008
DOI: 10.1029/2007wr006240
|View full text |Cite
|
Sign up to set email alerts
|

Spatial proximity, physical similarity, regression and ungaged catchments: A comparison of regionalization approaches based on 913 French catchments

Abstract: [1] Given the contradictory results from recent studies, this paper compares classical regionalization schemes of catchment model parameters over the wide range of hydroclimates found in France. To ensure the generality of the conclusions, we used two lumped rainfall-runoff models applied to daily data over a large set of 913 French catchments. Three types of approaches were considered: regionalization using regression, regionalization based on spatial proximity and regionalization based on physical similarity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
544
6
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 471 publications
(590 citation statements)
references
References 33 publications
35
544
6
5
Order By: Relevance
“…A comparison of the three methods mentioned above with two lumped conceptual models (GR4J and TOPMO) shows that in France, where the gauging network is relatively dense, spatial proximity provides the best regionalization results for a 913 catchments dataset (Oudin et al, 2008). It is argued that the failure of methods based on catchment descriptors might be attributable to the lack of key physical descriptors of soil hydrology, and that there is room for progress by learning how to merge the different methodologies.…”
Section: Regionalization Methods: a Compromise Between Available Physmentioning
confidence: 99%
See 2 more Smart Citations
“…A comparison of the three methods mentioned above with two lumped conceptual models (GR4J and TOPMO) shows that in France, where the gauging network is relatively dense, spatial proximity provides the best regionalization results for a 913 catchments dataset (Oudin et al, 2008). It is argued that the failure of methods based on catchment descriptors might be attributable to the lack of key physical descriptors of soil hydrology, and that there is room for progress by learning how to merge the different methodologies.…”
Section: Regionalization Methods: a Compromise Between Available Physmentioning
confidence: 99%
“…Among the numerous techniques proposed for the regionalization of catchment model parameters, generally for continuous (conceptual) rainfall runoff models, three kinds of approaches can be distinguished with their specific advantages and inherent drawbacks (Oudin et al, 2008): regression based methods, geographical proximity, and similarity methods. Several regionalization studies mostly for rather large datasets are briefly presented in (Table 2).…”
Section: Regionalization Methods: a Compromise Between Available Physmentioning
confidence: 99%
See 1 more Smart Citation
“…The calibrated parameters of the donor catchments are then transferred to the ungauged (receiver) catchments. The application of these methods in UK, Australia, and Indian, as well as other countries, has demonstrated that the former two approaches yield better results than the latter [22][23][24][25][26]. A combination of spatial proximity (distance) and physical similarity indices could therefore improve the accuracy of simulations [25].…”
Section: Introductionmentioning
confidence: 99%
“…The application of these methods in UK, Australia, and Indian, as well as other countries, has demonstrated that the former two approaches yield better results than the latter [22][23][24][25][26]. A combination of spatial proximity (distance) and physical similarity indices could therefore improve the accuracy of simulations [25]. For the stream flow prediction of ungauged catchments, the presence of well-gauged catchments in proximity is more beneficial than having physically similar catchments [24].…”
Section: Introductionmentioning
confidence: 99%